2021
DOI: 10.1111/jocd.14299
|View full text |Cite
|
Sign up to set email alerts
|

SULT1A1 (Minoxidil Sulfotransferase) enzyme booster significantly improves response to topical minoxidil for hair regrowth

Abstract: Minoxidil is the only topical drug approved by the US FDA to regrow hair. It is approved for use in men and women and is a ubiquitous over-the-counter product. Unfortunately, minoxidil has a relatively low efficacy rate. In clinical trials, minoxidil was shown to regrow hair in approximately 35% of subjects after 16 weeks of use. 1,2 Compliance with the 16-week topical regimen remains a major barrier to success, while 30%-40% of subjects in physician-guided studies report success, that number is drastically re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“… 117 In support of this theory is the benefit afforded with use of a newer formula that increases the activity of this enzyme in regrowing hair for males with androgenetic alopecia. 118 Multiple studies support efficacy of the 5% formulation in children and adults with patchy AA. 119 In a meta-analysis that included 6 studies ( n = 255), minoxidil use was associated with significant regrowth rates compared to placebo of 7.86 (95% 3.74,16.5).…”
Section: Minoxidilmentioning
confidence: 99%
“… 117 In support of this theory is the benefit afforded with use of a newer formula that increases the activity of this enzyme in regrowing hair for males with androgenetic alopecia. 118 Multiple studies support efficacy of the 5% formulation in children and adults with patchy AA. 119 In a meta-analysis that included 6 studies ( n = 255), minoxidil use was associated with significant regrowth rates compared to placebo of 7.86 (95% 3.74,16.5).…”
Section: Minoxidilmentioning
confidence: 99%
“…Minoxidil sulfate is the active metabolite required to exert the vasodilatory and hair-growing effects of minoxidil, and is catalyzed by SULT1A1 in the outer root sheath of suprabulbar hair follicles [33]. It is estimated that roughly 60% of the population has low SULT1A1 activity in their hair follicles, which is related to a decreased possibility that minoxidil will be effective in encouraging hair regrowth [34], [35].…”
Section: 4: Minoxidil E Cacymentioning
confidence: 99%
“…density and thickness of hair stay the same, as these patients are called non-responders. A small cohort study from 2022 showed the effectiveness of using a minoxidil adjuvant therapy [14]. Nowadays, booster-like substances are a subject of research, as most information about them is yet to be discovered.…”
Section: Minoxidilmentioning
confidence: 99%